2004
DOI: 10.1038/sj.onc.1207733
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell cycle-dependent degradation of c-Ski proto-oncoprotein by Cdc34

Abstract: It is known that excess amounts of Ski, or any member of its proto-oncoprotein family, causes disruption of the transforming growth factor beta signal transduction pathway, thus causing oncogenic transformation of cells. Previous studies indicate that Ski is a relatively unstable protein whose expression levels can be regulated by ubiquitin-mediated proteolysis. Here, we investigate the mechanism by which the stability of Ski is regulated. We show that the steady-state levels of Ski protein are controlled post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…This degradation seems to occur in G0/G1 phase, as the lowest levels of Ski were observed in those phases of the cell cycle. This result agrees with recently published data (Macdonald et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This degradation seems to occur in G0/G1 phase, as the lowest levels of Ski were observed in those phases of the cell cycle. This result agrees with recently published data (Macdonald et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Recently, Macdonald et al (2004) showed a higher stability of Ski protein in Xenopus egg extracts prepared from the mitotic phase of the cell cycle. Here we show that the highest levels of Ski and the phosphorylated form of Ski were present in nocodazole-prophase arrested cells, a time when the (Nigg, 2001), and that the Ski protein level correlated directly with the levels of cyclin B.…”
Section: Discussionmentioning
confidence: 99%
“…First, we established the dose-response relationship between TGF-␤ concentration and luciferase reporter activity in mink lung epithelial cells stably infected with a luciferase reporter gene driven by a Smad-sensitive promoter (hereafter referred to as PE25 cells [30]) (Fig. 1A).…”
Section: Tgf-␤ Concentration Is the Signal To Which Cells Respondmentioning
confidence: 99%
“…SnoN and Ski, two corepressors of transcription, are rapidly removed upon stimulation with TGF-␤ in order to initiate TGF-␤-induced transactivation. In particular, degradation of SnoN has been reported to require the involvement of anaphase-promoting complex/cyclosome (APC/C), whereas destruction of Ski is suggested to be through the SCF (Skp1-Cul1-F-box) complex (21,38,43). Our recent studies systematically measuring protein profiles in response to TGF-␤ stimulation show that several proteins are significantly altered in a rapid manner that suggests protein degradation (unpublished data).…”
mentioning
confidence: 99%